Indeks Prediktif Kejadian Schistosomiasis Berbasis Perilaku Masyarakat di Dataran Tinggi Lindu Kabupaten Sigi - Akbar, Hairil (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2019)
Schistosomiasis or also commonly called snail fever is a parasitic disease caused by trematodes worm infections of the genus Schistosoma japonica sp, with both male and female worms live in the mesenteric veins and urinary vessels. Hospes intermediary is snails from species Oncomelania hupensis lindoensis. The purpose of this study was to develop a predictive index based on community behavior on the incidence of Schistosomiasis in the Lindu Plateau, Sigi Regency. This study applied observational analytic study design using case control approach. The sample size consisted of 82 people representing 41 people in case group and 41 people in control group obtained using simple random sampling. The results of this study indicated eight candidates variables to be continued into multiple logistic regression, namely: level of education (p value = 0.065), occupation (p value = 0.165), history of Schistosomiasis (p value = 0.045), the use of latrines (p value = 0.043), the use of water resources (p value = 0.000), passing through the focus area (p value = 0.016), the use of personal protective equipment (p value = 0.002) and customary activity on the rivers/ditches (p value = 0.000). The predictive index on the incidence of Schistosomiasis based on community behavior is as follows (-2.780 + 2.322*The use of water resources (Severe) + 1.773*customary activity on the rivers/ditches (Yes) + 1.486*Passing through the focus area (Yes) + 1.419*The use of personal protective equipment (Not used)). Predictive index on the incidence of Schistosomiasis obtained in this study can be used as a measuring tool to help health personnels in conducting screening so as to reduce the spread and transmission of Schistosomiasis and to carry out early prevention. Keywords: Index, Schistosomiasis, Community behavior, Lindu